2009
DOI: 10.1051/forest/2009029
|View full text |Cite
|
Sign up to set email alerts
|

Drought susceptibility and recovery of transplanted Quercus rubra seedlings in relation to root system morphology

Abstract: Keywords:gas exchange / northern red oak / root growth / transplant shock / xylem water potential Abstract • Transplant shock, implicated by depressed seedling physiological status associated with moisture stress immediately following planting, limits early plantation establishment. Large root volume (Rv) has potential to alleviate transplant shock because of higher root growth potential and greater access to soil water.• We investigated impacts of drought and transplant Rv on photosynthetic assimilation (A), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 27 publications
2
25
1
2
Order By: Relevance
“…We observed in line with previous studies (Girard et al 1997a;McKay et al 1999;Yu et al 2003;Jacobs et al 2009) that air exposure immediately caused significant water loss of the plants although they were still in the dormant stage with fully closed buds. Bare-rooted beech plants are very sensitive to desiccation (McKay et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…We observed in line with previous studies (Girard et al 1997a;McKay et al 1999;Yu et al 2003;Jacobs et al 2009) that air exposure immediately caused significant water loss of the plants although they were still in the dormant stage with fully closed buds. Bare-rooted beech plants are very sensitive to desiccation (McKay et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the exceptional drought probably caused dieback, inhibited growth, and increased mortality of seedlings from both grades, because average size of trees from both grades was relatively large. Previous studies have found drought negatively impacted larger trees more than smaller trees, but their seedlings sizes were much smaller than in this study [25,56]. Perhaps, the lack of inclusion of cull seedlings in both grades also equalized response to planting shock.…”
Section: Discussioncontrasting
confidence: 65%
“…This finding was surprising given multiple studies that found increased transplant shock for larger seedlings [25,26,28,56]. However, we were approaching significance in survival differences between grades in the shelterwood harvest stand in year 2 (premium grade = 74 percent ± 3.6 versus standard = 64 percent ± 3.9), and in stem dieback in the midstory removal stand across years (premium grade = 23 percent ± 2.2 versus standard 17 percent ± 2.1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The first physiological symptom of transplanting shock is the lowering in predawn water potential. As water potential becomes more negative, other physiological symptoms appear like reduced stomatal conductance, photosynthesis, transpiration and growth (Grossnickle, 1988;Guehl et al, 1989;Jacobs et al, 2009;Sands, 1984). These symptoms were observed by Mena-Petite et al (2005) after transplanting seedlings of Pinus radiata both under drought and under well-watered conditions.…”
Section: Problems During the Forest Establishmentmentioning
confidence: 99%